(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This study focuses on the duties and responsibilities of heads of teacher educationinstitutions to ensure the smooth functioning of teacher education programs. The role of institutionalleaders is critical to sustaining quality teacher education, managing resources effectively, fostering apositive learning environment, and fostering continuous improvement. The importance of teachereducation programs to produce competent and qualified teachers. It then details the specific roles andresponsibilities of the head of an educational institution, including curriculum development andimplementation, faculty management, student guidance and support, and building partnerships withrelevant stakeholders. This includes setting clear goals, establishing policies and procedures, andensuring compliance with regulatory requirements. Institution leaders play a key role in creating apositive and inclusive learning environment that fosters collaboration, innovation and professionalgrowth for both faculty and students.